A Robotic Experiment Toward Understanding Human Gas-Source Localization Strategies - Góngora González, Andrés; González-Monroy, Javier; González-Jiménez, Antonio Javier (My University, 2017)
This paper describes an experiment for gas-source localization with a human-teleoperated mobile robot devised to gather data on how humans search for odor-sources. To that end, more than 150 repetitions of the search process are recorded for 69 test subjects, under 4 sensor configurations (including electronic nose, anemometer and video camera) and 4 scenarios (i.e. with different wind-flow conditions and gas-source position). The experiment has been carried out with a ROS-based simulator that allows driving the robot while recording data of interest (e.g. driving commands, robot localization, sensor measurements, groundtruth, etc.) for further analyzing the human process of gas-source searching, and computational fluid dynamics (CFD) to generate realistic and repeatable test conditions. The manuscript describes the different environmental parameters and sensor combinations of the experiment, and explains the methodology under which it was executed. The obtained dataset is publicly available at http://mapir.isa.uma.es/mapirwebsite/index.php/253-gsl-dataset.
Keywords: Robots autónomos; Mobile Robot; Electronic Nose; Gas Source; Robot Teleoperation